Interactions between CNS and immune cells in tuberculous meningitis - Ma, Quan; Chen, Jinyun; Kong, Xingxing; Zeng, Yuqin; Chen, Zhanpeng; Liu, Huazhen; Liu, Lanlan; Lu, Shuihua; Wang, Xiaomin (Frontiers in Immunology, 2024)
The central nervous system (CNS) harbors its own special immune system composed of microglia in the parenchyma, CNS-associated macrophages (CAMs), dendritic cells, monocytes and the barrier systems within the brain. Recently, advances in the immune cells in the CNS provided new insights to understand the development of tuberculous meningitis (TBM), which is the predominant form of Mycobacterium tuberculosis (M.tb) infection in the CNS and accompanied with high mortality and disability. The development of the CNS requires the protection of immune cells, including macrophages and microglia, during embryogenesis to ensure the accurate development of the CNS and immune response following pathogenic invasion. In this review, we summarize current understanding the CNS immune cells during the initiation and development of the TBM. We also explore the interactions of immune cells with the CNS in TBM. In the future, the combination of moder techniques should be applied to explore the role of immune cells of CNS in TBM.